Mesenchymal stem cells: a new trend for cell therapy - Wei Xin; Yang Xue; Han Zhi-peng; Qu Fang-fang; Shao Li; Shi Yu-fang (Acta Pharmacologica Sinica; Vol 34, No 6 (June 2013): Acta Pharmacologica Sinica (Special Feature: Stem cell therapy and drug discovery), 2016)
Xin WEI1, Xue YANG2, Zhi-peng HAN3, Fang-fang QU3, Li SHAO1 , *, Yu-fang SHI2, * 1Renji Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai 200127, China; 2Key Laboratory of Stem Cell Biology, Institute of Health Sciences, Shanghai Jiao Tong University School of Medicine, Shanghai 200025, China; 3Tumor Immunology and Gene Therapy Center, Eastern Hepatobiliary Surgery Hospital, the Second Military Medical University, Shanghai 200433, China Mesenchymal stem cells (MSCs), the major stem cells for cell therapy, have been used in the clinic for approximately 10 years. From animal models to clinical trials, MSCs have afforded promise in the treatment of numerous diseases, mainly tissue injury and immune disorders. In this review, we summarize the recent opinions on methods, timing and cell sources for MSC administration in clinical applications, and provide an overview of mechanisms that are significant in MSC-mediated therapies. Although MSCs for cell therapy have been shown to be safe and effective, there are still challenges that need to be tackled before their wide application in the clinic. Keywords: mesenchymal stem cell; cell therapy; tissue injury; degenerative disease; immune disorder; graft-versus-host disease; immunomodulation; trophic factor This project was supported by the Key Basic Research Project of China (Grant No 2011CB966200, 2010CB945600, and 2011CB965100); Key Project of the National Natural Science Foundation of China (Grant No 81030041); the National Natural Science Foundation of China (Grant No 31171321 and 81101622); Special Funds for the National Key Sci-Tech Special Project of China (Grant No 2012ZX10002-016 and 2012ZX10002011-011); the Shanghai Science and Technology Committee (Grant No 11ZR1449500 and 12ZR1439800); and the Science Fund for Creative Research Groups, NSFC, China (Grant No 81221061). * To whom correspondence should be addressed. E-mail drshaoli@sina.com (Li SHAO); shiyufang2@gmail.com (Yu-fang SHI) Received 2013-03-11 Accepted 2013-04-05